Modelling and performance analysis of smart waste collection system: a Petri nets and discrete event simulation approach. (12th November 2019) - Benarbia, Taha; Darcherif, Abdel Moumen; Sun, Daniel Jian
With the recent development of smart cities all over the world, many new performance services have been developed, including smart mobility, energy and waste collection. In general, waste collection operators face the challenge of routing management, so as to reduce the costs of transportation and energy consumption. This paper proposes a waste collection strategy model based on real time inventory control of the vehicles' routing problem, with stochastic Petri nets (PN). The developed model and simulations show the capability of using PN models to predict the critical situations, analyse collection strategy efficiency, and improve performance. Results from the numerical example indicate that the overall vehicle travel distance for waste collection has been significantly reduced by estimating the exact moment to launch the collection service, as well as resolves conflict between vehicles during the collection. Simulation scenarios were introduced to assess the real time impact by monitoring the collection process.